Acceptabilité et mise en œuvre des politiques de relocalisation face aux risques littoraux : perspectives issues d’une recherche en partenariat - Camille André; Paul Sauboua; Hélène Rey-Valette; Gaëlle Schauner (VertigO)
This paper examines the feasibility conditions for the relocation measures proposed in the context of climate-change-related sea-level rise. The authors discuss innovative implementation and funding arrangements to suggest ways to help local authorities develop protocols for action. The discussion begins by considering the principles which will change the perception of such relocations into integrated territorial reorganization projects. This approach enables operations to be divided into different modules that must be planned and coordinated. The authors then explore possible compensation and temporary occupancy mechanisms in order to increase acceptability and reduce the need for public funding. Finally, a simulation is presented of the funding needs in the case of two representative archetypes: a neighbourhood and a coastal community. Some thought is also given to the need for regulatory development in order to reduce the institutional constraints that currently exist in the case of France.